Korelasi Gaya Hidup dan Stres Pada Penderita Hiperkolesterolemia - Ferdy Lainsamputty; Nova Gerungan (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Dyslipidemia causes high mortality worldwide, about 4 million per year. The lifestyle of patients with high cholesterol levels tends to be poor which has the potential to trigger cardiovascular disease. Chronic stress in this population is also suspected to be associated with a poor lifestyle. Aim: To investigate the relationship between lifestyle and stress in patients with hypercholesterolemia. Methods: A descriptive correlational and cross-sectional design were applied with 53 respondents. The questionnaires used were Health-Promoting Lifestyle Profile (HPLP II) and Perceived Stress Scale (PSS). Results: There was no significant association between lifestyle and overall stress. The stress management domain had a significant correlation with stress. Conclusion: Hypercholesterolemic patients who had good control of psychological conditions, also experienced lower stress levels.